2018
DOI: 10.1007/s11250-018-1615-6
|View full text |Cite
|
Sign up to set email alerts
|

Livestock and livelihoods of smallholder cattle-owning households in Cambodia: the contribution of on-farm and off-farm activities to income and food security

Abstract: The majority of smallholder farming households in Cambodia are rurally based and rely on agriculture to support their livelihoods. However, in recent years, growth in the agriculture sector has stagnated with farmers facing several challenges including declining prices for traditional crops and irregular rainfall patterns. This has led to a need for farmers to diversify income sources with livestock promoted as a more viable livelihood activity, particularly the raising of cattle and poultry. However, uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…The study intended to identify opportunities for improving FMD vaccination uptake and implementing biosecurity interventions in rural communities. The study identified that although smallholder farmers undertake a range of farming and off-farming activities, large ruminants contribute a large proportion of total household income (KC 30%; PS 25%) at the rural community level (Ashley et al, 2018;Samkol et al, 2015) and deserve investments to mitigate disease risk, despite the majority of surveyed farmers still practicing the traditional method of cattle raising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study intended to identify opportunities for improving FMD vaccination uptake and implementing biosecurity interventions in rural communities. The study identified that although smallholder farmers undertake a range of farming and off-farming activities, large ruminants contribute a large proportion of total household income (KC 30%; PS 25%) at the rural community level (Ashley et al, 2018;Samkol et al, 2015) and deserve investments to mitigate disease risk, despite the majority of surveyed farmers still practicing the traditional method of cattle raising.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving adequate vaccination coverage to produce effective herd immunity, both nationally and within villages, is a major challenge in Cambodia (Sieng & Kerr, 2013), with vaccination coverage of the national large ruminant population estimated 2% in 2010 (Young, Suon, Leong et al., 2013). Farmers generally have a poor understanding of the need for FMD vaccination and have financial constraints that limit investments in disease risk management (Ashley et al., 2018; Young et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From livelihood assets, improved livestock husbandry contains poultry, apiary, fattening practice (of cattle, sheep, & goat), and horse and donkeys for transportation. It could be promoted as a preferred livelihood activity as it is a superior income source due to higher returns and lower variable costs [12]. Livestock husbandry contributes more (sell milk and fattened livestock to meat) to total household income, constitutes an important safety net during times of economic hardship, is used as traditional means of transportation (donkey and horse), and draught power for farming, and produce dung for household energy and as organic fertilizer [12,35].…”
Section: Assets Possessionmentioning
confidence: 99%
“…It could be promoted as a preferred livelihood activity as it is a superior income source due to higher returns and lower variable costs [12]. Livestock husbandry contributes more (sell milk and fattened livestock to meat) to total household income, constitutes an important safety net during times of economic hardship, is used as traditional means of transportation (donkey and horse), and draught power for farming, and produce dung for household energy and as organic fertilizer [12,35]. The value of productive livestock husbandry is found to be significantly associated with the probability of a household generating sustainable livelihood [15,44,59].…”
Section: Assets Possessionmentioning
confidence: 99%
“…Cattle provide an important source of income to small-holder farmers in sub-Saharan Africa, however infectious diseases pose a major challenge to the industry through economic losses and concerns on human health [9,19]. Certain indigenous cattle breeds have acquired tolerance to a number of diseases through a better capacity to control parasitemia and limit anemia development [4,8].…”
Section: Introductionmentioning
confidence: 99%